Comparative Analysis of Revenue Growth and Profitability among Renewable Energy Companies in India - Dinesh V B S Yakkala; Mr. Bipul Kumar (International Journal of Scientific Research in Science and Technology, 2025)
India's renewable energy sector has achieved substantial growth, spurred on mainly by the lures of public policy and private investment. This paper shall compare revenue growth and profitability of four big players in the sector—Adani Green Energy, Suzlon Energy, Inox Wind, and Borosil Renewables—using important financial ratios: EBITDA margin, ROE, and EPS. From the findings, Adani Green excels in revenue generation but has lower profitability compared to others, Suzlon has just recovered from a downward turn due to various circumstances, while Borosil also witnessed a growth pattern. Inox Wind exhibits varied results in performance. Efficiency in operations, access to capital, and the influence of the regulatory framework appear to have major weight in determining profitability. Sustainable financial strategies and policy measures will be crucial to ensuring long-term survival of enterprises in the sector. Directions for future research should include non-financial factors that provide a wider range of background and perspective in the ailing sector.